Lesson Study as A Pattern of Professional Development Teacher - Santoso, Erik (Universitas Muhammadiyah Surakarta, 2019)
The problem of the weakness of the learning process cannot only be completed in a short time. Therefore, it needs an ongoing activity in the development of teacher professionalism. One of them is through Lesson study activities. Lesson study is basically an activity carried out by the teacher in order to improve the learning process where the focus of attention is on student activities. Through lesson study, it is hoped that there will be a better learning process. The information from lesson study activities consists of planning (plan), implementation (do), reflection (see). All three can be carried out properly in a slklus so that the learning process can correct properly. In the plan the teacher plans to start from making lesson design, chapter design to the students' thinking trajectory. Careful planning will make it easier for teachers to carry out learning well. Planning is better to involve peers so there is input from peers about the content of the material. In the process of implementing strength there is an observation so that it is allowed to observe. bring the form of a camera or something else to record all student activities and learning processes. Reflection activities are activities that discuss the implementation of learning and are focused on student activities. Through development activities such as lesson study, it is expected to improve teacher professionalism